Predstavitev sodobne slikanice v Italiji - Zudič Antonič, Nives; Sossi, Livio (Revija za elementarno izobraževanje, 2018)
Presentation of the Contemporary Picture Book in Italy. The aim of this research was to examine the connection between the originality level in children's expression during visual art lessons and their level of tolerance for difference. The participants comprised primary school pupils from grades one, two and three, a total of 110. It was confirmed that there was a statistically significant difference between the pupils whohad an introduction to the lesson using the didactic model of visual problembased teaching and those who had not. Learning and setting art terminology, the analysis of motifs and explanation, as well as  demonstration of art techniques resulted in a higher level of creativity in visual performance, as well as a higher level of tolerance. It can be concluded that, with the proper choice of didactic models in teaching the visual arts, a wide range of pupil attitudes and beliefs can be improved.
Keywords: visual art didactics; tolerance; originality; stereotype; children's drawing